Adolescent Marriage as the Impact of Social Change in Society and Implications in Guidance and Counseling - Anggia Wahyu Agustin; Firman Firman; Riska Ahmad (Jurnal Neo Konseling, 2021)
Adolescence is one period in the range of human life. Teenagers can be said to be individuals who have experienced puberty. However, in fact many adolescents marry at a relatively young age, this marriage is caused by several factors which are the result of social changes. Social change is all changes in social institutions in a society, which affect the social system, including values, attitudes and patterns of behavior among community groups. This paper to describe how many factors that cause adolescent marriage in the community. Data is collected by reviewing and / or exploring several journals, books, research results, and documents (both printed and electronic) as well as data sources and or other information deemed relevant to the study to be discussed which is Implication in Guidance and Counseling to accordance with the problems that happen in marriage.